Arlington Park: Variations on Virginia Woolf’s Mrs Dalloway - Monica LATHAM (E-REA)
Arlington Park was written in the wake of Virginia Woolf’s Mrs Dalloway: the style and texture of Rachel Cusk’s writing is very much reminiscent of her predecessor’s prose. The contemporary author uses Woolfian features and templates (“Dallowayisms” Chatman 274) and transposes them to the present-day novel that dissects domestic middle-class suburban life. Just like Mrs Dalloway, Cusk’s observational novel drifts through time and consciousness. The novel is made up of an accumulation of little snippets of life (“patches of life,” Arlington Park 220) and the narrative switches between various characters that lead subjective and introspective “Woolfian” lives, microscopically observed by the narrator who renders their obsessive self-analysis and interrogations. Cusk’s novel focuses on the overwhelming awareness of the moment and the passage of time with its layers and thickness. It deals with what goes unsaid under the surface: fleeting moods, thoughts and unspoken communication. Like Woolf, Cusk offers the reader a multitude of aural and visual perceptions – the sensory impressionism chiselling out inner turmoil –, and has a cult for the object and for the powerful, arresting triviality of the non-event. The contemporary author shares with her predecessor the art of scrutinising material details using the same sharp eye with which she explores the characters’ minds. Besides, Cusk’s epiphany bears resemblance to the Woolfian “moment of being,” the various refrains and repetitions give her prose a musical quality, and her characters constantly attempt to give a definition of the texture of life and reality. Thus, Arlington Park constitutes a twenty-first-century cover version of Mrs Dalloway. I would like to observe Cusk’s narrative, stylistic and thematic features, which seem to situate her novel at the confluence of two traditions: firstly, her writing stems from modernism and prolongs modernist techniques, more particularly the Woolfian legacy; Cusk can thus be said to be a neo-modernist writer.2 Secondly, her work belongs to the current “literary fiction” genre: it is an elitist, lyrical, “writerly” type of fiction born with modernist aesthetics.